“Efecto de diferentes dosis de enmienda calcio magnésica y niveles de abonamiento en el rendimiento del café (coffea arabica L.) en condiciones del alto mayo – San Martín” - García Castro, Dante Horacio (2004)
In order to evaluating the effect of different dose of amendment calcium magnésica (Magnecal) and security levels in the yield of the coffee (Arabic Coffea), variety " Pache " under conditions of the High May and to determine the relationship benefits cost of the best treatment for the experimental conditions carried out; the present investigation work was executed in land of Mr. Antonio Herrera Arévalo, located to the smallest Populated Center close The Future" - Km 8 - Highway President Fernando Belaunde Terry- Rioja - Elm trees; which presents an Altitude of 864 m. s. n. m.; longitude west 77° 1477'' and a south latitude of 06° 00'32"; likewise politically located in the smallest Populated Center The Future, County of Rioja, Region San Martin. He presents work he/she behaved at random under a design of complete blocks with factorial arrangement of 4 (Dose of amendment calciUm magnésica) for 2 (fertilization Levels). The results demonstrated that for the heights difference statistic didn't exist for the interactions which the heights vary from 1,83 to 1,98 m. For other the plants demonstrated to be more resistant to more dose of amendment caicium magnésica, likewise the doses· of amendment calcium magnésica demonstrated statistical ; significancia, the yields demonstrated to go in increase with the source of NPK 120- 110-184 which the yields varied from 53,93 to 53,86 q/ha. The biggest utilities were obtained with applications of NPK: 60-55-92 varying of S l. 847, 15 to 606, 1 O new suns.